Applied anatomic and phylogenetic considerations of surgical and regional nerve block landmarks on the skull and mandibles of two hystricomorphs; the crested porcupine (Hystrix cristata) and greater cane rat (Thryonomys swinderianus) - Michael O. Samuel; I. Aboh Kisani (Elsevier, 2020)
This investigation seeks to discriminate variations in anatomic landmarks of regional nerve block/surgical importance in skulls of two phylogenetically related laboratory species; the Old-world porcupines (H. cristata) and Cane rat (T. swinderianus), and comparedfrontal sinus shape outline architecture in mid-sagittal section for both. Using Generalized Procrustes Analysis, the study utilized thirty-seven and forty-eight skull samples of each respectively. for landmarks assessments in right lateral, ventral and right lateral hemi-mandibular views, and Elliptical Fourier analyses for frontal sinus contours. Extremely significant (P ≤ 0.0001) interspecies landmark size variations were observed with Mahalanobis distance of 1.89, 2.03 and 2.06 for the evaluated positions respectively, mean centroid size ranged from 3200 mm in H. cristata to 1400 in T. swinderianus. Shape regression model suggested similar allometric pattern except in mandibles (λ Wilks 0.96, F 44.55) but (λ Wilks 0.88, F 127.9) between species. EFA descriptors demonstrated. amplitude associated attenuations in harmonic values (factor about 1/8 to 1/22,000) with angular orientation in major axes values reduced by not more than ¼ after size normalization. PC1 & 2 contributed 81.19%, 6.29% but 100% in within and between species analysis. Stepwise harmonic increments outline reconstructions demonstrated disparities up to the 6th harmonics with marginally lower variance value in cane rats (1.37) than in porcupines (1.68). The results conclude that skull shape and size disparities observed suggest despite similar phylogeny both are diverse and does not compare in structural and frontal sinus outline shapes.